Energy Consumption, Renewable Energy Transition, and Industrial Production as Determinants of Economic Growth in Kazakhstan: An ARDL Analysis - Tastanbekova, Karlygash; Myrzabekkyzy, Kundyz; Lukhmanova, Gulnar; Pirmanova, Zhansulu; Izatullayeva, Bibigul; Duisenbek, Daniyal (International Journal of Energy Economics and Policy, 2026)
This study examines the dynamic interrelationships between energy consumption, renewable energy transition, and industrial production as key drivers of Kazakhstan’s economic growth over the period 2000-2024. Drawing on annual data and econometric analysis, the research investigates both short- and long-term linkages among these variables. The findings indicate that energy consumption and industrial output exert strong positive effects on GDP, emphasizing their central role in supporting Kazakhstan’s sustained economic expansion. In contrast, renewable energy consumption shows a weak and statistically insignificant effect, which reflects its relatively small share in the national energy mix but also signals untapped potential for future development. The results of diagnostic and stability tests confirm the robustness of the model, suggesting that while Kazakhstan’s growth has been primarily supported by industrial activity and traditional energy sources, greater diversification toward renewables could strengthen long-term resilience and sustainability. Overall, the study highlights the need for continued industrial modernization, enhanced energy efficiency, and strategic investment in clean energy technologies to promote balanced, inclusive, and environmentally sustainable economic growth.